2018
DOI: 10.1016/j.electacta.2018.02.121
|View full text |Cite
|
Sign up to set email alerts
|

Formation of needle-like and honeycomb-like magnesium oxide/hydroxide structures by electrodeposition from magnesium nitrate melts

Abstract: The processes of electrochemical deposition of magnesium oxide/hydroxide on glassy carbon (GC) electrode from magnesium nitrate hexahydrate melt have been investigated. A novel procedure predicting a possibility of direct formation of magnesium oxide during electrodeposition from the nitrate melt used is reported. XRD analysis of the obtained deposits showed the formation of magnesium oxide along with magnesium hydroxide. The electrodeposition of magnesium oxide/hydroxide commences in magnesium underpotential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 51 publications
(103 reference statements)
2
28
1
Order By: Relevance
“…In the anodic scan, there were no current waves which would indicate the oxidation complementary to the two cathodic current waves. Thеsе recordings were in a very good agreement with our previous results, obtained on GC electrode in the same melt [7][8][9][10] where starting potential has been E s = 1.400 V vs. Mg/Mg 2+ .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In the anodic scan, there were no current waves which would indicate the oxidation complementary to the two cathodic current waves. Thеsе recordings were in a very good agreement with our previous results, obtained on GC electrode in the same melt [7][8][9][10] where starting potential has been E s = 1.400 V vs. Mg/Mg 2+ .…”
Section: Resultssupporting
confidence: 89%
“…In contrast to the experimental conditions applied in our earlier work, 8,10 in linear sweep voltammetry experiments (LSV), the potential was swept from starting potential, E S, being 0.000 V to a final cathodic potential, E C, of -1.000 V vs. Mg/Mg 2+ , and back to E S . Experiments under the potentiostatic regime were carried out at: -0.200 V vs. Mg/Mg 2+ , -0.700 V vs. Mg/Mg 2+ and -1.000 V vs. Mg/Mg 2+ applied to the working electrode at T = 373 K. Also, in all electrodeposition processes, the deposition charges were limited to 2 C. After electrolysis, the working electrode was taken out from the cell, rinsed with absolute ethanol (Zorka--Pharma, Šabac, Serbia) and dried at room temperature.…”
mentioning
confidence: 99%
“…The XRD analysis of products of molten salt electrolysis of magnesium nitrate hexahydrate showed that the mixture of MgO/Mg(OH)2 was formed [39,40]. The network of the intertwined needles was formed in the UPD (underpotential) region (Fig.…”
Section: Molten Salt Electrolysismentioning
confidence: 99%
“…The hole size decreased, while their number increased with increasing the overpotential of electrodeposition (13c and d). [39].…”
Section: Molten Salt Electrolysismentioning
confidence: 99%
See 1 more Smart Citation